Association Between Lateralized Periodic Discharge Amplitude and Seizure on Continuous EEG Monitoring in Patients With Structural Brain Abnormality in Critical Illness - Fatima, Safoora; Sun, Mengzhen; Gjini, Klevest; Struck, Aaron F. (Frontiers in Neurology, 2022)
Objective: To investigate the association between lateralized periodic discharge (LPD) amplitude and seizure risk on an individual level. Methods: Retrospective case–control study of patients undergoing continuous EEG monitoring was performed. We included 10 patients with LPDs and seizures as cases and 10 controls, patients with LPDs without seizure. Analysis was performed with a mixed effects model with primary outcome measure of number of seizures per 8-hour EEG epoch with fixed effects being variables of interest and random effect being subject ID. Results: Epochs with seizures showed a higher absolute amplitude (corrected p=0.04) and a higher relative amplitude (corrected p=0.04) of LPDs. Additionally, the number of seizures was higher in epochs that had LPDs with plus features (uncorrected p=0.002) and LPDs with higher relative amplitude (uncorrected p=0.005). Conclusion: Higher LPD amplitude is associated with increased risk of seizures on an individual patient level. A decreasing amplitude is suggestive of decreasing cortical irritability, decreasing seizure risk, and may in fact be suggestive of decreasing ictal like behavior of LPDs.